Of Nation and People: The Discursive Logic of Nationalist Populism - Anastasiou, Michaelangelo (Javnost-The Public, 2019)
The present article develops a theory of “nationalist populism” by examining the relationship between populism and the hegemonic configuration of nation-states. Following recent contributions by the “Essex School,” populism is understood as a process whereby diverse political demands and identities come to be aggregated via signifiers, typically that of “the people,” that incarnate an antagonistic populist body. I argue that the rhetorical construction of “the people,” to the extent that it is executed in the context of national hegemonic blocs, will often (inadvertently) come to be overdetermined by uncontested nationalist narratives and life modalities that are symbolically associated with the hegemonic signifier “the nation.” Nationalist populism can therefore best be understood as a chimeric political logic, whereby a populist totality is parasitically signified vis-à-vis the hegemonic signifier “the nation” and its associated family resemblances. This logic can assume a variety of forms, its content being dependent upon contextual political and ideological considerations.